The intertemporal supply of natural resources and the recycling of Hotelling rents: The case of the Saudis - Horst Siebert (Universität Mannheim, Institut für Volkswirtschaftslehre und Statistik, Sonderforschungsbereich 5: Staatliche Allokationspolitik im marktwirtschaftlichen System, 1981)
In this paper, we consider the case of a resource-exporting country that invests part of its resource earnings in the international capital market. We can show that the recycling of Hotelling rents introduces an incentive to supply more resources today and thus alleviates the resource shortage for the present generation. But the other side of the coin is that scarcities in the future will be more severe, that quantities extracted will decline more rapidly, that exhaustion will occur at an earlier date and that the price of the natural resource will rise faster. The paper also shows that the introduction of a capital market with a given interest rate separates the problem of optimal consumption and the optimal intertemporal supply of natural resources.
Keywords: 330